Demetallization of Enterococcus faecalis biofilm: a preliminary study - Carlos ESTRELA; Rodrigo COSTA E SILVA; Roberta Cerasi URBAN; Pablo José GONÇALVES; Júlio A. SILVA; Cyntia R.A. ESTRELA; Jesus Djalma PECORA; Ove A. PETERS (University of São Paulo, 2018)
Abstract Objectives To determine the concentration of calcium, iron, manganese and zinc ions after the application of chelator to Enterococcus faecalis biofilms. Material and Methods Fifty bovine maxillary central incisors were prepared and inoculated with E. faecalis for 60 days. The following were used as irrigation solutions: 17% EDTA (pH 3, 7 and 10), 2.5% sodium hypochlorite (NaOCl) combined with 17% EDTA (pH 3, 7 and 10), distilled water (pH 3, 7 and 10), and 2.5% NaOCl. Each solution was kept in the root canal for five minutes. Fifteen uncontaminated root canals were irrigated with 17% EDTA (pH 3, 7 and 10). Six teeth were used as bacterial control. The number of calcium, iron, manganese and zinc ions was determined using flame atomic absorption spectrometry. Mean ± standard deviation (SD) values were used for descriptive statistics. Results Calcium chelation using 17% EDTA at pH 7 was higher than at pH 3 and 10, regardless of whether bacterial biofilm was present. The highest concentration of iron occurred at pH 3 in the presence of bacterial biofilm. The highest concentration of manganese found was 2.5% NaOCl and 17% EDTA at pH 7 in the presence of bacterial biofilm. Zinc levels were not detectable. Conclusions The pH of chelating agents affected the removal of calcium, iron, and manganese ions. The concentration of iron ions in root canals with bacterial biofilm was higher after the use of 17% EDTA at pH 3 than after the use of the other solutions at all pH levels.